High performance free-standing films by layer-by-layer assembly of graphene flakes and ribbons with natural polymers - Moura, Duarte Alexandre Campos Serra (2016)
In this work, novel free-standing (FS) films based on chitosan, alginate and graphene oxide (GO) were developed through layer-by-layer assembly. First, GO was synthesized from graphite and multi-walled carbon nanotubes using a modified Hummer's method, yielding oxidized graphene flakes (o-GFs) and oxidized graphene nanoribbons (o-GNRs), respectively, which were then characterized. Then FS films were produced and their morphological, thermal and mechanical properties, as well as the o-GF and o-GNR dispersion along the films were assessed. Their degradation and swelling profiles as well as their biological behavior were evaluated. Graphite and nanotubes were successfully oxidized and exfoliated forming stable suspensions that could be combined with chitosan (CHI) and alginate (ALG) solutions by layer-by-layer processing. The addition of o-GFs and o-GNRs resulted in rougher, hydrophilic FS films with significantly improved mechanical properties relative to CHI/ALG films. The presence of o-GFs or o-GNRs did not affect the thermal stability and the addition of o-GFs resulted in films with enhanced cytocompatibility. The results demonstrate the high potential of the GO reinforced films for biomedical applications, in particular o-GF films, for wound healing, and cardiac and bone engineering applications.